Warm Compress Of Pain Level In Patients Elderly Who Suffers Rematic - Firdaningsih; Amirullah; A.Nurlaela Amin (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2019)
The background based on data found at the society health center of Bontonyeleng, district of Gantarang, the regency of Bulukumba.it received 45 rheumatic patients in 2017. The aim of this research is to find out the influence of warm compress to decrease the pain degree of rheumatic patients qat society health center of Bontonyeleng, district of Gantarang, the regency of Bulukumba. The method has taken in this research was experimental research ( pre-experimental design) using the one-group pretest-posttest design. The population sample in this research was 30 respondent, it was taken using shack formula. Data analyse result using T-test match with value p 0,000. the research result gained before applying warm compress ton lo pain degree patients are 2 respondents or (6.7%) medium paint degree patient is 28 respondents or (93,3). While the result after applying a warm compress for low pain degree patients is 20 respondents or (66.7%) medium pain degree patient is 10 respondents or (33.3%). Based on explanations above, we can conclude that there is the influence of warm compress to decrease pain degree for the rheumatic patient especially for old society at society heald center of Bontonyeleng, district of Gantarang, the regency of Bulukumba so that is why people in bukit harapan village, district of Gantarang, regency of Bulukumba suggests for those who feel the pain that indicates rheumatic should not ignore and do an action like applying warm compress immediately using correct tools to decrease the pain or doing health check as soon as possible to nearby medical care.